2022
DOI: 10.1590/interface.210724
|View full text |Cite
|
Sign up to set email alerts
|

Territórios rurais contra a Covid-19: saberes, fazeres e reflexões por meio da Educação Popular em Saúde

Abstract: Este artigo se apoia na sistematização de experiências de Oscar Jara para reconstruir os caminhos de uma pesquisa-ação participativa em saúde nas comunidades rurais com base em experiências de prevenção e cuidado à saúde no enfrentamento da Covid-19. Desde junho de 2020 temos desenvolvido experiências de Educação Popular em Saúde (EPS) no campo, pautadas pela pedagogia freiriana nos territórios do norte e na baixada litorânea do estado do Rio de Janeiro, especificamente áreas de reforma agrária vinculadas ao M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Apparently, the emergency PAA, identified as the main measure in supporting family farmer's members, had little reach in the studied region. The study by Alves et al (2022), with territories and rural collectives, showed that communities had the suspension or reduction of value of contracts for food access programs, such as PNAE.…”
Section: Public Policies Food and Nutritional Security And Social Ass...mentioning
confidence: 99%
“…Apparently, the emergency PAA, identified as the main measure in supporting family farmer's members, had little reach in the studied region. The study by Alves et al (2022), with territories and rural collectives, showed that communities had the suspension or reduction of value of contracts for food access programs, such as PNAE.…”
Section: Public Policies Food and Nutritional Security And Social Ass...mentioning
confidence: 99%